A Study to Assess the Proarrhythmic Potential of Mirtazapine Using Concentration‐QTc (C‐QTc) Analysis. Issue 4 (27th July 2018) - Gurkan, Sevgi; Liu, Fang; Chain, Anne; Gutstein, David E.
Abstract: Most new chemical entities with systemic availability are required to be tested in a study specifically designed to exclude drug‐induced corrected QT interval (QTc) effects, the so‐called thorough QT/QTc study. Mirtazapine (Remeron™) is an antidepressant indicated for the treatment of episodes of major depression, which was originally approved in 1994 without a thorough QT study. To evaluate the proarrhythmic potential of mirtazapine, we performed a QT/QTc study with a novel design including implementation of an analysis of the relationship between drug concentration and the QTc interval as the primary assessment of proarrhythmic potential of mirtazapine. The least squares mean differences of the corrected QT interval between mirtazapine and placebo at the geometric mean maximum concentration of drug in blood plasma (90% confidence interval) were 2.39 milliseconds (0.70, 4.07) at the 45‐mg dose and 4.00 milliseconds (1.18, 6.83) at the 75‐mg dose level of mirtazapine. Modeling of the concentration/QTc relationship for moxifloxacin confirmed that the assay method was adequately sensitive. This trial showed a positive relationship between mirtazapine concentrations and prolongation of the QTc interval. However, the degree of QT prolongation observed with both 45‐mg and 75‐mg doses of mirtazapine was not at a level generally considered to be clinically meaningful. This study further demonstrates that analysis of the relationship between drug concentration and the QTc interval may be a reasonable alternative to traditional TQT studies to assess risk of QT prolongation.